Maternal Nutrition During Late Gestation and Lactation: Association With Immunity and the Inflammatory Response in the Offspring - Li, Qihui; Yang, Siwang; Zhang, Xiaoli; Liu, Xinghong; Wu, Zhihui; Qi, Yingao; Guan, Wutai; Ren, Man; Zhang, Shihai (Frontiers in Immunology, 2022)
The immature immune system at birth and environmental stress increase the risk of infection in nursing pigs. Severe infection subsequently induces intestinal and respiratory diseases and even cause death of pigs. The nutritional and physiological conditions of sows directly affect the growth, development and disease resistance of the fetus and newborn. Many studies have shown that the provision of nutrients such as functional oligosaccharides, oils, antioxidants, and trace elements could regulate immunity and the inflammatory response of piglets. Here, we reviewed the positive effects of certain nutrients on milk quality, inflammatory response, oxidative stress, and intestinal microflora of sows, and further discuss the effects of these nutrients on immunity and the inflammatory response in the offspring.